Exploring the Ultimate Regime of Turbulent Rayleigh-Bénard Convection Through Unprecedented Spectral-Element Simulations - Jansson, Niclas; Karp, Martin; Perez, Adalberto; Mukha, Timofey; Ju, Yi; Liu, Jiahui; Páll, Szilárd; Laure, Erwin; Weinkauf, Tino; Schumacher, Jörg; Schlatter, Philipp; Markidis, Stefano (Proceedings of the International Conference for High Performance Computing, Networking, Storage and Analysis, SC 2023, 2023)
We detail our developments in the high-fidelity spectral-element code Neko that are essential for unprecedented large-scale direct numerical simulations of fully developed turbulence. Major innovations are modular multi-backend design enabling performance portability across a wide range of GPUs and CPUs, a GPU-optimized preconditioner with task overlapping for the pressure-Poisson equation and in-situ data compression. We carry out initial runs of Rayleigh-Bénard Convection (RBC) at extreme scale on the LUMI and Leonardo supercomputers. We show how Neko is able to strongly scale to 16,384 GPUs and obtain results that are not possible without careful consideration and optimization of the entire simulation workflow. These developments in Neko will help resolving the long-standing question regarding the ultimate regime in RBC.
CRIS-Team Scopus Importer:2023-12-22